Trends in novel psychoactive substance use and the impact of Irish legislative efforts (UCC Student Medical Journal, 2024)
Introduction: Novel Psychoactive Substances (NPS) are emerging at increasingly rapid rates, creating unpredictability in drug markets and ineffective drug policies. Ireland has a drug-induced mortality rate greater than three times the European average and the highest rate of NPS use. Given the scarcity of published literature, the National Advisory Committee on Drugs has recommended trends in NPS use be studied in order to facilitate appropriate public health measures. Objectives: To critically evaluate the published literature on NPS and establish the health risks associated with their use, trends in drug-induced fatalities, and the efficacy of legislative policies in reducing NPS consumption.Methods: A systematic search of Medline and PubMed was completed based on pre-defined inclusion criteria, and relevant studies were selected for comprehensive analysis. Results: Clinical experiences of NPS abusers predominantly involved neurological or psychological symptoms, coupled with cardiovascular effects. While the overall prevalence of NPS presentations in Europe remains low, fatal overdoses were primarily attributed to acute overdose and commonly involved ingestion of synthetic cathinones. Legislation in 2010 resulted in decreased rates of recent and problematic NPS use, along with higher rates of negative user experiences. No significant displacement towards established illicit drugs was reported. Conclusion: This systematic review has demonstrated the current state of knowledge regarding NPS within an Irish context. The trends in NPS prevalence and toxicity are important considerations for the development of effective drug monitoring or enforcement strategies. This knowledge is further relevant for emergency physicians and forensic pathologists in order to make accurate medical assessments.
Keywords: novel psychoactive substances; NPS; public health; public health policy